2016
DOI: 10.1021/jacs.6b08802
|View full text |Cite
|
Sign up to set email alerts
|

Selective Catalytic Reduction of N2 to N2H4 by a Simple Fe Complex

Abstract: The catalytic fixation of N by molecular Fe compounds is a rapidly developing field, yet thus far few complexes can effect this transformation, and none are selective for NH production. Herein we report that the simple Fe(0) complex Fe(EtPCHCHPEt)(N) (1) is an efficient catalyst for the selective conversion of N (>25 molecules N fixed) into NH, attendant with the production of ca. one molecule of NH. Notably, the reductant (CoCp*) and acid (PhNHOTf) used are considerably weaker than conventional chemical H and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
143
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 25 publications
(28 reference statements)
8
143
0
Order By: Relevance
“…2f,17 These reactions highlight the far superior N 2 RR activity of [ Os ]-N 2 − by comparison to either [ Ru ]-N 2 − or [Fe]-N 2 − . Thus, treatment of a suspension of [ Os ]-N 2 − in Et 2 O at −78 °C with 46 equiv of [H 2 NPh 2 ][OTf| and 50 equiv of Cp* 2 Co results in the generation of 7.1 ± 0.6 equiv of NH 3 per Os (Table 1, entry 6; 46% based on acid).…”
mentioning
confidence: 83%
“…2f,17 These reactions highlight the far superior N 2 RR activity of [ Os ]-N 2 − by comparison to either [ Ru ]-N 2 − or [Fe]-N 2 − . Thus, treatment of a suspension of [ Os ]-N 2 − in Et 2 O at −78 °C with 46 equiv of [H 2 NPh 2 ][OTf| and 50 equiv of Cp* 2 Co results in the generation of 7.1 ± 0.6 equiv of NH 3 per Os (Table 1, entry 6; 46% based on acid).…”
mentioning
confidence: 83%
“…Such conditions additionally afford unusually high selectivity and catalytic turnover for NH 3 . 20 Moreover, we note that the use of milder reagents as reductant ( E 0 ; eq 1) and acid (p K a ; eq 1) engenders a higher effective bond dissociation enthalpy (BDE effective ; eq 1). 15,21 This may in turn afford access to proton-coupled electron transfer (PCET) pathways (e.g., FeN 2 + H • → FeN 2 H) in addition to electron transfer (ET)/proton transfer (PT) pathways, thus enhancing overall catalytic efficiency.…”
mentioning
confidence: 96%
“…Theoretical considerations, including DFT calculations, and experimental details are discussed that suggest the viability of a decamethylcobaltocene-mediated PCET pathway in this system; by extension we suggest that metallocene-mediated (e.g., Cp* 2 Cr) PCET pathways may be operative in previously studied Mo and Fe N 2 -fixing systems that use metallocene reductants. 1013,20 …”
mentioning
confidence: 99%
“…1 Only a few Fe-containing compounds have been reported that are capable of mediating the catalytic reduction of N 2 using chemical H + and esources, 2,3 and we recently reported that the simple Fe(0) phosphine complex Fe(depe) 2 (N 2 ) [1; depe = Et 2 PCH 2 CH 2 PEt 2 ] mediates the efficient catalytic reduction of N 2 in conjunction with excess acid and reductant; this was the first system using a molecular TM compound which was selective for N 2 H 4 production over NH 3 . 4 Nevertheless, mechanistic details for these N 2 to N 2 H 4 /NH 3 conversions remain scarce, mostly due to rapid reaction rates and the high lability of the various FeN x H y intermediates. 5 In particular, examples which establish the structural and electronic changes upon mono-protonation of Fe-ligated N 2 to form diazenide species (Fe-NN-H) remain elusive to date.…”
mentioning
confidence: 99%